Processo de seleção de fornecedores em uma empresa do setor automotivo - Guerhardt, Flávio (2014)
This study aims to discuss the tools and criteria generally used in the selecting suppliers process, listing what are the most applied which are used together and how which criteria are relevant in this process. Supplier selection has been considered as a very important issue in various industries, especially in the automotive market. For supplier selection it is important to standardize tools and criteria used to ensure that personal opinions do not influence the choice. This research aims, through a case study to present and to analyze a method and criteria for supplier selection used in a supply chain member of the Brazilian automotive market. With the presentation and analysis of the used method is expected to contribute to companies to have better conditions to decide by the supplier that best meets their expectations.